Analisis Kualitas Udara Pada Rumah Warga Terhadap Parameter Bakteri dan Jamur - Novia Dwi Astuti; Sri Hastutiningrum*; Sudarsono Sudarsono (Jurnal Teknologi, 2022)
The final processing and disposal the waste occurs at the Final Disposal Facility (TPA). Because the rubbish heaps include a variety of contaminants and produce air pollution, landfills can have an impact on the environment's quality. This study intends to identify and contrast the outcomes of the analysis of the air quality in residents' homes near the Piyungan TPA location, which is 50 m, 350 m, 650 m, and 1000 m from the TPA, with quality standards according to the Decision of the Minister of Health No. 1077 of 2011 based on bacterial and fungal parameters. The ideal distance between residential areas and the TPA location is another goal of this study. Air sampling at each location used the air sampling method directly with NA media and PDA media in petri dishes. The results showed that the number of bacterial colonies at a distance of 50 m was 4,485.6 CFU m-3 and the fungal colonies were 2,306.4 CFU m-3. At a distance of 350 m, the number of bacterial colonies was 3,355.4 CFU m-3 and fungal colonies were 2,130.9 CFU m-3. The number of bacterial colonies at a distance of 650 m was 2,919.7 CFU m-3 and the number of fungal colonies was 2,001.3 CFU m-3. The number of bacterial colonies at a distance of 1000 m was 1,353.2 CFU m-3 and the number of fungal colonies was 765.2 CFU m-3. Air quality in residents' homes with a distance of 50 m to 1000 m does not meet the healthy air quality requirements based on Minister of Health Regulation No. 1077 of 2011 concerning Indoor Air Conditioning at Home with maximum levels of airborne microbes <700 CFU m-3.